The need for inclusion of integrated teaching on refugee and asylum seeker health in undergraduate medical curriculum - Pittala, Rajeshwari; Jacob, Wright (Frontiers in Education, 2023)
Introduction: Providing care for refugees and asylum seekers requires special knowledge and training. Refugees and asylum seekers often have unique health needs that require specialised care. Purpose: This research focused on the need and relevance of incorporation of refugee and asylum seekers’ health in undergraduate medical curriculum teaching at King’s College London GKT Medical School. Methods: A mixed method approach was adopted involving review of available literature on refugee health in the medical curriculum, followed by interview and e-survey on the perspectives of tutors and students, respectively. Discussion: The research points to an overwhelming agreement on the need, learning outcomes and challenges of integrating refugee and asylum seeker health into undergraduate medical and dental education both from the perspectives of clinical teachers and medical students. Conclusion: A collaborative approach involving students, teachers and refugee stakeholders will help in developing an effective refugee curriculum to provide equitable healthcare in the UK.